EMPOWERING DIGITAL SOCIAL MEDIA IN ORGANIZING COMPUTER SCIENCE STUDENTS HIGHER EDUCATION ASSIGNMENTS - Abdillah, Leon A. (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Information technology has transformed higher education in various sectors, including academic field. This study discusses how blog by using WordPress facilitate online activity in computer science and information systems college students. The research objective to be achieved by the researchers through the research, are as follows: 1) Utilizing DropBox & WordPress as a media for students assignments online, 2) How to make use of social technologies in the education athmosphere, and 3) Identify the features or facilities that could be used for the implementation of an online assignments. Observation was conducted with 93 second year students as respondents. Author develops the virtual class blog page by using WordPress, and Facebook to disseminate assignments instructions. Research findings show that male students are more dominant in this scheme. Social information technology likes WordPress and Facebook have many rich features in supporting virtual class activity for computer science students. The use of WordPress, Facebook, and DropBox can create an atmosphere of assignments and teamproject more modern, efficient, and environmentally friendly